2005
DOI: 10.1111/j.1365-2966.2005.09244.x
|View full text |Cite
|
Sign up to set email alerts
|

The open-cluster initial--final mass relationship and the high-mass tail of the white dwarf distribution

Abstract: Recent studies of white dwarfs in open clusters have provided new constraints on the initial–final mass relationship (IFMR) for main‐sequence stars with masses in the range 2.5–6.5 M⊙. We re‐evaluate the ensemble of data that determines the IFMR and argue that the IFMR can be characterized by a mean IFMR about which there is an intrinsic scatter. We investigate the consequences of the IFMR for the observed mass distribution of field white dwarfs using population synthesis calculations. We show that while a lin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
204
4
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(245 citation statements)
references
References 27 publications
20
204
4
1
Order By: Relevance
“…The cluster data for NGC 3532 are from Koester & Reimers (1993), although we have used the latest results of Koester & Reimers (1996) and those reported in Ferrario et al (2005). According to Ferrario et al (2005) the age of this cluster is 300±150, and the metallicity is [Fe/H]= −0.022 (Twarog et al 1997) or [Fe/H]= −0.02 (Chen et al 2003), so we have used the tracks corresponding to Z = 0.019.…”
Section: Other Available Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The cluster data for NGC 3532 are from Koester & Reimers (1993), although we have used the latest results of Koester & Reimers (1996) and those reported in Ferrario et al (2005). According to Ferrario et al (2005) the age of this cluster is 300±150, and the metallicity is [Fe/H]= −0.022 (Twarog et al 1997) or [Fe/H]= −0.02 (Chen et al 2003), so we have used the tracks corresponding to Z = 0.019.…”
Section: Other Available Datamentioning
confidence: 99%
“…According to Ferrario et al (2005) the age of this cluster is 300±150, and the metallicity is [Fe/H]= −0.022 (Twarog et al 1997) or [Fe/H]= −0.02 (Chen et al 2003), so we have used the tracks corresponding to Z = 0.019. We have also included the data for the three white dwarfs reported in Reimers & Koester (1989), although the resolution is lower.…”
Section: Other Available Datamentioning
confidence: 99%
See 1 more Smart Citation
“…This yielded a value of M MS = 3.8 ± 0.5 M . Alternatively, we used the IFMR determined by Ferrario et al (2005) based on white dwarfs observed in open clusters (see in particular their Fig. 1).…”
Section: The Optical Spectrum Of Hip 96515 B: Observations and Modelingmentioning
confidence: 99%
“…assessment of cluster's age and metallicity, amount of convective overshooting, thickness of the white dwarf H/He layers, The IFMR of Single CO White Dwarfs 37 Figure 1. Semi-empirical IFMR based on the compilation by Ferrario et al (2005), Kalirai et al (2008), andCatalán et al (2008). Solid lines are linear fits provided by various authors quoted in the plot.…”
Section: Introductionmentioning
confidence: 99%